The level of DLDB/CHIP controls the activity of the LIM homeodomain protein Apterous: evidence for a functional tetramer complex in vivo - Rincón-Limas, Diego E. (Oxford University Press, 2000)
The LIM homeodomain (LIM-HD) protein Apterous (Ap) and its cofactor DLDB/CHIP control dorso- ventral (D/V) patterning and growth of Drosophila wing. To investigate the molecular mechanisms of Ap/CHIP function we altered their relative levels of expression and generated mutants in the LIM1, LIM2 and HD domains of Ap, as well as in the LIM-interacting and self-association domains of CHIP. Using in vitro and in vivo assays we found that: (i) the levels of CHIP relative to Ap control D/V patterning; (ii) the LIM1 and LIM2 domains differ in their contributions to Ap function; (iii) Ap HD mutations cause weak dominant negative effects; (iv) overexpression of ChipΔSAD mutants mimics Ap lack-of-function, and this dominant negative phenotype is caused by titration of Ap because it can be rescued by adding extra Ap; and (v) overexpression of ChipΔLID mutants also causes an Ap lack-of-function phenotype, but it cannot be rescued by extra Ap. These results support the model that the Ap–CHIP active complex in vivo is a tetramer.